COMPREHENSIVE REVIEW OF COMMUNITY HEALTH WORKER PROGRAMS AND ASSESSING ROLES, TRAINING, AND IMPACT ON POPULATION HEALTH OUTCOMES - Mana Yahya Mishaa Al Busus, Ali Yahya Shaghath, Nasser Saleh Ali Al Mergan, Hussain Mohammad Hamad Almnsour, ‏Salem Ali Harmal Bani Salman, Matared Ali Hamad Alyami, Mohammed Hussain Ali Aljarah, Mahdi Shatwi Saud Alyami (Chelonian Research Foundation, 2022)
CHWs (community health workers) have gained recognition as vital constituents of community health requirements in all countries, including disadvantaged communities. This exhaustive process will analyze the roles, training modes, and influence of CHW in promoting public health. This review begins with thoroughly inspecting relevant articles, highlighting many of CHW's most successful program indicators and suggesting several improvement opportunities for their optimal functioning. The results point out that CHW's activities are fundamental in upholding health equity and improving health conditions, only presenting the need to carry out further research and give CHWs adequate support and training. Keywords: community health workers, CHW programs, healthy populations, health equity,